2011
DOI: 10.5194/acp-11-12865-2011
|View full text |Cite
|
Sign up to set email alerts
|

Growth rates of nucleation mode particles in Hyytiälä during 2003−2009: variation with particle size, season, data analysis method and ambient conditions

Abstract: Abstract. The condensational growth rate of aerosol particles formed in atmospheric new particle formation events is one of the most important factors influencing the lifetime of these particles and their ability to become climatically relevant. Diameter growth rates (GR) of nucleation mode particles were studied based on almost 7 yr of data measured during the years 2003-2009 at a boreal forest measurement station SMEAR II in Hyytiälä, Finland. The particle growth rates were estimated using particle size dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
166
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(211 citation statements)
references
References 84 publications
25
166
6
Order By: Relevance
“…In this case the particle growth rates as function of particle size was determined to be 2.2 nm h -1 , 2.8 nm h -1 and 3.2 nm h -1 in size ranges <3nm, 3-7 nm and 7-15 nm. The increased growth rate of the larger particles is similar to many observations of atmospheric particle growth rates [2].…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…In this case the particle growth rates as function of particle size was determined to be 2.2 nm h -1 , 2.8 nm h -1 and 3.2 nm h -1 in size ranges <3nm, 3-7 nm and 7-15 nm. The increased growth rate of the larger particles is similar to many observations of atmospheric particle growth rates [2].…”
Section: Resultssupporting
confidence: 71%
“…Various volatile organic compounds (VOCs) are emitted by vegetation, and in the atmosphere these VOCs are oxidized mainly by ozone, OH and NO 3 into lower volatility compounds that are able to condense on particles. From long-term observations at a boreal forest station in Central Finland, it has been observed that particle growth rates are clearly highest at summertime at the same time as emissions of VOCs are also largest during the year [2].…”
Section: Introductionmentioning
confidence: 99%
“…Yli-Juuti et al (2011) also observed a correlation between monoterpene concentrations and 7-20 nm particle growth in the boreal forest site of Hyytiälä, Finland, indicating the importance of monoterpene oxidation products in the growth process. Also, a clear seasonal variation in the growth of 3-20 nm particles was observed in Hyytiälä, with highest values during the summer Hirsikko et al, 2005;Riipinen et al, 2011;Yli-Juuti et al, 2011). The growth of the smallest sub-3 nm particles in Hyytiälä, on the other hand, has not been observed to show such seasonality (Hirsikko et al, 2005;Yli-Juuti et al, 2011).…”
Section: S a K Häkkinen Et Al: Semi-empirical Parameterization Ofmentioning
confidence: 85%
“…Several recent observations from different field sites suggest that the condensational growth rates of ambient nanoparticles increase with particle size (Hirsikko et al, 2005;Manninen et al, 2010;Yli-Juuti et al, 2011;Kuang et al, 2012). Yli-Juuti et al (2011) also observed a correlation between monoterpene concentrations and 7-20 nm particle growth in the boreal forest site of Hyytiälä, Finland, indicating the importance of monoterpene oxidation products in the growth process.…”
Section: S a K Häkkinen Et Al: Semi-empirical Parameterization Ofmentioning
confidence: 91%
See 1 more Smart Citation